W cieniu Anny Frank. Szanse Żydów na przeżycie w okupowanej Holandii - Bob Moore (Zagłada Żydów)
During the German occupation of the Netherlands between 1940 and 1945, around 75% of the country’s Jewish population were deported and killed, primarily in the extermination camps of Auschwitz and Sobibor. Much attention has been paid to the factors which explain this, but this article questions how any Jews managed to survive in an increasingly hostile environment where there were no ‘favorable factors’ to aid them. The analysis centers on the attitudes of the Jews towards acting illegally, their relationships with the rest of Dutch society, and the possible opportunities for escape and hiding. It also looks at the myriad problems associated with the day-to-day experiences of surviving underground